Estudo da viabilidade de produção do biodiesel obtido através do óleo de fritura usado na cidade de Santa Maria - RS - Castellanelli, Carlo Alessandro (2008)
The utilization of biodiesel has shown a promising potential in the whole world. Firstly, for it s enormous contribution to the environment, due the qualitative and quantitative reduction s levels of environmental pollution, and, secondly, as a strategic source of renewable energy to replace diesel and other oil derivatives. In this context the used frying oil takes place, as a raw material that can be processed into a high quality biodiesel, and that once was being wasted and dumped in the environment in a erroneous way. This dissertation presents a feasibility study of producing biodiesel obtained through the used frying oil in the city of Santa Maria, Rio Grande do Sul, Brazil. Some topics was analyzed for an effective scheme for the collection and production of biodiesel. The downtown of the city was chosen for the study, being the most populous and the neighborhood and for having more establishments using the fried oil in its processes, that way, making the results more reliable. Questionnaires were applied to the establishments and to the local population concerning the actions on the final destination of this waste, as well as environmental perceptions and knowledge about the theme, and also to determine the volume of used oil that would be ready for collection and processing into biodiesel. After that, was developed an economical viability of the project, from the perspective of the a public institution of education s perspective, the Federal University of Santa Maria, and this way, the project can reach benefits besides the environmental, social and financial ones, it can promotes an academic integration with the project, being a source of learning and development. Results demonstrated to be highly economical favourable to the implementation of the proposed scheme, however, to optimize the donation and collection system of the used oil, finally, were proposed some ideas and actions for the project s efficiency from the beginning of its chain.